What Do Mothers (or Caregivers) Know about Their Children's Oral Hygiene? An Update of the Current Evidence - Riccardo Aiuto; Mario Dioguardi; Silvia Caruso; Erica Lipani; Dino Re; Roberto Gatto; Daniele Garcovich (MDPI AG, 2022)
Tooth decay remains one of the most common diseases in children, although it is a preventable injury and despite significant advances that has been made in terms of attention and care for oral hygiene. Several studies have shown the association between prevalence of tooth decay in children and parents' incorrect oral care habits, with a low educational level and a low socioeconomic background. The question that arises concerns the actual oral hygiene knowledge of mothers, fathers, family members or caregivers of young patients; therefore, the aim of this review is to investigate the genesis of gaps in the topic. A literature search was conducted through the Scopus and PubMed search engine and ended in May 2022; only studies from the past 20 years were included. Current evidence suggests that parents and caregivers still have little knowledge about their children's oral health: there is not enough awareness about the importance of preventing oral diseases, due to poor attention to good oral hygiene but also lack of information from health professionals and institutions. In the future, all the professionals involved in the pregnant woman's care should increase parents' knowledge, solve their doubts, collect and compare data in order to design effective intervention programs.